The Role of Palliative Care in Population Management and Accountable Care Organizations - Smith, Grant (J Palliat Med, 2015)
By 2021, health care spending is projected to grow to 19.6% of the GDP, likely crowding out spending in other areas. The 2010 Affordable Care Act (ACA) attempts to curb health care spending by incentivizing high-value care through the creation of Accountable Care Organizations (ACOs), which assume financial risk for patient outcomes. With this financial risk, health systems creating ACOs will be motivated to pursue innovative care models that maximize the value of care. Palliative care, as an emerging field with a growing evidence base, is positioned to improve value in ACOs by increasing high-quality care and decreasing costs for the sickest patients. ACO leaders may find palliative care input valuable in optimizing high-quality patient-centered care in the accountable care environment; however, palliative care clinicians will need to adopt new models that extrapolate their direct patient care skills to population management strategies. We propose that palliative care specialists take on responsibilities for working with ACO leaders to broaden their mission for systemwide palliative care for appropriate patients by prospectively identifying patients with a high risk of death, high symptom burden, and/or significant psychosocial dysfunction, and developing targeted, “triggered” interventions to enhance patient-centered, goal-consistent, coordinated care. Developing these new population management competencies is a critical role for palliative care teams in the ACO environment.